2017
DOI: 10.1093/jb/mvx008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of the actin-binding ability of the fission yeast α-actinin, Ain1, in vitro and in vivo

Abstract: A contractile ring (CR) is involved in cytokinesis in animal and yeast cells. Although several types of actin-bundling proteins associate with F-actin in the CR, their individual roles in the CR have not yet been elucidated in detail. Ain1 is the sole α-actinin homologue in the fission yeast Schizosaccharomyces pombe and specifically localizes to the CR with a high turnover rate. S. pombe cells lacking the ain1+ gene show defects in cytokinesis under stress conditions. We herein investigated the biochemical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For instance, the K255E mutation was located at the interface between the two CH domains, and it abnormally enhances actin-binding activity . Further, we and the other study demonstrated that the mutation (R216E) on Ain1 causes the deformation of the CR. , However, there is insufficient evidence about whether the closed–open conformational change exists. It is still unknown how the R216E mutation alters the actin-binding affinity.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…For instance, the K255E mutation was located at the interface between the two CH domains, and it abnormally enhances actin-binding activity . Further, we and the other study demonstrated that the mutation (R216E) on Ain1 causes the deformation of the CR. , However, there is insufficient evidence about whether the closed–open conformational change exists. It is still unknown how the R216E mutation alters the actin-binding affinity.…”
Section: Introductionmentioning
confidence: 57%
“…When α-actinin forms an antiparallel dimer, the EF-hand motif of a pair α-actinin molecule is adjacent to ABD . Actually, the preceding study reported that the abnormal affinity of Ain1 R216E to F-actin is restored with the deletion of the EF-hand …”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Compared to fimbrin Fim1, α-actinin Ain1 is a relatively weak F-actin bundling protein (Addario et al, 2016; Li et al, 2016; Morita et al, 2017). Remarkably, low-speed sedimentation (Figure 6A,B) and TIRFM assays (Figure 6C,D, Figure 6—video 1) revealed that tropomyosin Cdc8 significantly enhances the F-actin bundling ability of Ain1.…”
Section: Resultsmentioning
confidence: 99%